2012
DOI: 10.1007/s00442-012-2267-2
|View full text |Cite
|
Sign up to set email alerts
|

Exotic herbivores on a shared native host: tissue quality after individual, simultaneous, and sequential attack

Abstract: Plants in nature are often attacked by multiple enemies whose effect on the plant cannot always be predicted based on the outcome of individual attacks. We investigated how two invasive herbivores, the hemlock woolly adelgid (Adelges tsugae) (HWA) and the elongate hemlock scale (Fiorinia externa) (EHS), alter host plant quality (measured as amino acid concentration and composition) when feeding individually or jointly on eastern hemlock (Tsuga canadensis), an important long-lived forest tree that is in severe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
58
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(63 citation statements)
references
References 55 publications
4
58
1
Order By: Relevance
“…A major finding in this study is that AG herbivores can reduce the growth of their conspecifics only when they colonized plants before the conspecifics arrived on the plant. Similar sequence-specific effects have been reported previously (Viswanathan et al 2007;Poelman et al 2008;Gomez et al 2012). In contrast to these studies that mostly reported changes in concentrations of defense compounds or primary assimilates, I did not observe altered concentrations of IGs by AG herbivory in plant foliage (Figure 2.3).…”
Section: Timing Of Attack By Aboveground and Belowground Herbivores Osupporting
confidence: 87%
See 1 more Smart Citation
“…A major finding in this study is that AG herbivores can reduce the growth of their conspecifics only when they colonized plants before the conspecifics arrived on the plant. Similar sequence-specific effects have been reported previously (Viswanathan et al 2007;Poelman et al 2008;Gomez et al 2012). In contrast to these studies that mostly reported changes in concentrations of defense compounds or primary assimilates, I did not observe altered concentrations of IGs by AG herbivory in plant foliage (Figure 2.3).…”
Section: Timing Of Attack By Aboveground and Belowground Herbivores Osupporting
confidence: 87%
“…Interestingly, several studies have shown that concentrations of defense compounds in a plant may only change in response to the first attacker and may not be modified by later arrivers (Viswanathan et al 2007;Poelman et al 2008;Erb et al 2011;Gomez et al 2012). As the defense response of a plant strongly depends on the identity of the first attacker (Voelckel and Baldwin 2004;Viswanathan et al 2007), the performance of an insect on a plant may depend both on the identity of the other herbivores on that plant, and on when they have been feeding on the plant (Poelman et al 2008;Gomez et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Because woody plants commonly function near the level of catastrophic xylem failure [24], when soils are dry, the difference of −0.5 MPa between the least and most infested classes of trees may mean that trees at the highest level of infestation are approaching or crossing a critical threshold. However the lower water potential we observed in infested trees may also be the result of osmotic adjustment as the tree acclimates; large increases in proline, commonly used for osmotic adjustment, have been found in infested trees [25]. Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…While HWA causes limited damage to Tsuga hosts in its native range of East Asia and the American Pacific Northwest (Lagalante and Montgomery 2003;Montgomery et al 2009;Oten et al 2012), HWA poses a serious threat to the host species, eastern hemlock (T. canadensis) and Carolina hemlock (T. caroliniana), in its introduced range (McClure 1991;Orwig and Foster 1998;Orwig et al 2002). Eastern and Carolina hemlock are also colonized by a second introduced piercing-sucking insect, the elongate hemlock scale (EHS, Fiorinia externa), which contributes to hemlock decline, but may deter later co-infestation by HWA (Gomez et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Infestation by HWA has been shown to alter xylem growth and water relations in eastern hemlock (Domec et al 2013;Gonda-King et al 2012). This effect is associated with a hypersensitive response (Radville et al 2011), reduced photosynthetic productivity (Domec et al 2013), and mobilization of nitrogen to new-growth tissues (Gomez et al 2012). In addition, infested hemlocks display a local increase in phenolic compounds (Pezet et al 2013), and a simultaneous increase in monoterpene volatilization and decrease in stored mono-and sesquiterpenes (Broeckling and Salom 2003;Pezet et al 2013).…”
Section: Introductionmentioning
confidence: 99%